Media and politics in Japan - Pharr, Susan J.; Krauss, Ellis S. (Book collections on Project MUSE., 1996)
Japan is one of the most media-saturated societies in the world. The circulations of its "big five" national newspapers dwarf those of any major American newspaper. NHK, its public service broadcasting agency, is second only to the BBC in size. And it has a full range of commercial television stations, high-brow and low-brow magazines (from widely read intellectual journals to the ubiquitous manga, or adult comic books), and a large antimainstream media and mini-media. Japanese elites, surveys show, rate the mass media as the most influential group in Japanese society. But what role do they play in political life? Whose interests do the media serve? As Japan's critics often hold, are they mainly servants of the state? Or are they watchdogs on behalf of the public, as the media themselves claim and as suggested by their role in uncovering late eighties and early nineties political scandals and in triggering political change in the summer of 1993? And what effects do the media have on the political beliefs and behavior of ordinary Japanese people? These questions, central for interpreting the media's role in any industrial society, are the focus of this collection of essays by leading political scientists, sociologists, social psychologists, and journalists. Japan's unique kisha (press) club system, its powerful media business organizations, the uses of the media by Japan's wily bureaucrats, and the role of the media in everything from political scandals to shaping public opinion, are among the many subjects of this insightful and provocative book.